Prinsip Hukum Pelayanan Perizinan Terpadu Satu Pintu (PTSP) di Indonesia - Pung Karnantohadi* (Universitas Airlangga, 2018)
This research entitled “Law Principle of One-Stop Integrated Service”. The preambule of the 1945 Constitution of the Republic of Indonesia mandated that the objective of the establishment of the Republic of Indonesia was to advance public welfare and educate the life of the nation. The mandate implies that the state is obliged to fulfill the needs of every citizen through a system of government that supports the creation of excellent public services in order to meet the basic needs and civil rights of every citizen of public goods, public services, and administrative services.The philosophical foundation of the obligation of every person to have permission to carry out their activities is contained in the provisions of Article 28J paragraph (1) of the 1945 Constitution of the Republic of Indonesia (Amendment), which aims to respect the human rights of other people in an orderly society, nation and state. In accordance with the provisions of Article 28 Paragraph (2) of the 1945Constitution of the Republic of Indonesia (Amendment), permission is a limitation of one's right to provide facilities to the community in the One Stop Integrated Service (PTSP) in the provisions of Article 28 H paragraph (2) The Republic of Indonesia in 1945 (Amendment), which reads